HMRC v Weald Leasing Ltd. Not only artifical: the abuse of law test in VAT - de la Feria, R (2008)

(untitled)
Comments on the Chancery Division decision in Weald Leasing Ltd v Revenue and Customs Commissioners on whether a leasing arrangement made by a partially exempt body seeking to defer the payment of irrecoverable VAT passed the EC abuse of rights test established in Halifax Plc v Customs and Excise Commissioners (C-255/02). Considers the impact of the decision on the development of the abuse of rights test in English case law in terms of the importance of the first element of the test and the concept of "normal commercial operations".